New approach to determining the economic efficiency of investments in mineral resources deposits development - V. M. Serov; Yu. P. Tikhonov (Вестник университета)
The purpose of the study is to develop methodological support for assessing the economic efficiency of investment when implementing projects for mineral deposits development, including investments in coal deposits development. Specific features of the content of these projects implementation process have been considered both in terms of investment result and its components, and in terms of composition and investment structure, which affect the methodology used and the corresponding methods of efficiency indicators calculation. The author’s approach and specific formulas for assessing the economic efficiency of investment when implementing projects for mineral deposits development have been outlined and substantiated. The projects are based on the use of newly created value indicator such as internal income of enterprises and organizations as a result of investment and investment activity. In its economic content it corresponds to the country’s internal national income indicator, which is the financial basis for the functioning and existence of the state. The formulas for calculating the indicators of economic efficiency of investments and capital investments in development and exploitation of mineral deposits of specific investors without considering the costs of production and social infrastructure have been given.